Is Frailty Syndrome a Predictor of Morbimortality in Postoperative Cardiac Surgery? – A Retrospective Cohort Study - Nascimento,Daniela Meirelles do (2022)
Abstract Background Frailty is a biological syndrome suggested as a better predictor of morbimortality than chronological age. Objective To assess associations between frailty and morbimortality outcomes in postoperative cardiac surgery. Methods A retrospective cohort study was conducted with cardiac surgery patients. Frailty and maximal inspiratory pressure (MIP) were assessed before surgery. Postoperative outcomes were: extracorporeal circulation time; use of vasopressor; mean arterial pressure (MAP); red blood cell (RBC) transfusion; cardiac arrhythmia and/or heart arrest; presence of intra-aortic balloon pump; antibiotic use; extubation time; length of stay in the intensive care unit (ICU); length of postoperative stay; mortality. One-way ANOVA was used to compare postoperative variables between frailty categories; Spearman was used to evaluate the correlations between frailty and postoperative variables. Age, sex, and MIP were introduced into multiple regression models to find the independent association between postoperative variables and frailty. A significance level of p < 0.05 was adopted. Results The medical records of 200 patients were analyzed (65.7±7.2 years; 68.5% men; 63.5% non-frail, 22.5% pre-frail, 14% frail). Frailty was not a predictor of postoperative outcomes. Age was an independent predictor for alterations in MAP (PR: 1.028, 95% CI: 1.003-1.053, p=0.025), need for RBC transfusion (PR: 1.034, 95% CI: 1.007-1.062, p=0.014), longer extubation time (PR: 1.052, 95% CI: 1.023-1.083, p<0.001), length of stay in the ICU (ß: 0.031, 95% CI: 0.010-0.053, p=0.005), length of postoperative stay (ß: 0.017, 95% CI: 0.003-0.031, p=0.015). Conclusions Frailty was not a predictor of morbimortality following cardiac surgery in middle-aged and older adults; however, age did predict morbidities in this setting.